Preparation of Fluoropgypsum Based Cementitious Material - Niu, Yiming; Chen, Shiying (International Journal of Materials Science and Technology Studies, 2025)
In order to realize the resource utilization of fluoropygite, the gelling material was prepared by using fluoropygite, fly ash and calcium carbide slag as composite raw materials. The optimal ratio was optimized by single factor test and orthogonal test, and the hydration mechanism and curing effect of fluoride ion were studied. The results show that the optimal ratio of strength for 3 days is fly ash: fluoropyssum: calcium carbide slag = 50:30:20,7 days the optimal ratio of strength is fly ash: fluoropyssum: calcium carbide slag = 50:25:15,28 days the optimal ratio of strength is fly ash: fluoropyssum: calcium carbide slag =60:30:15. By XRD and SEM analysis, the addition of calcium carbide slag has a certain curing effect on fluorine ions in fluoropogon.